PENERAPAN PROTOKOL KESEHATAN PADA SISWA SMA PEKANBARU PADA PEMBELAJARAN TATAP MUKA DI SAAT PANDEMI COVID-19 - Dessy Magdalena Menci; Ririn Muthia Zukhra; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The lack of implementation of health protocols in face-to-face learning can cause the spread of Covid-19 to be out of control. Phenomena that can be seen from the application of health protocols in face-to-face learning include students who do not maintain a safe distance, do not wash their hands with soap according to the provisions, do not use masks properly and correctly, and gather together. This study aims to describe the application of health protocols to SMA Negeri 8 Pekanbaru students in face-to-face learning during the Covid-19 pandemic. This study used a descriptive research design. The sample in this study was 173 people who were taken by random sampling technique. Data collection was taken using a health protocol implementation questionnaire. Data analysis using univariate. The results showed that the description of the application of health protocols for students of SMA Negeri 8 Pekanbaru in face-to-face learning during the Covid-19 pandemic was in the poor category (50.9%). The application of health protocols to students of SMA Negeri 8 Pekanbaru is not good and still needs to be improved, starting with restrictions, not changing every 4 hours, and not storing masks properly and correctly.Keywords: health protocol, students’ high school, face-to-face learning